CIVIL SERVICE DISCIPLINE BASED ON THE GOVERNMENT REGULATION NUMBER 53 YEAR 2010 VIEWED FROM THE PERSONEL LAW ASPECT IN INDONESIA - Gusti Lanang Rakayoga (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Stressing toward civil servant discipline in the era of reformation and autonomy by government is a positive response to achieve a world class governance of Indonesia government. Based on the view,  it can be formulated problem as follows as: How is the regulation of civil servant discipline in the laws in Indonesia? How is the procedure of civil servant disciple sanction in Indonesia? This research is a normative law research with using law,  conceptual,  and case approach. From the research can be concluded as follows as: (1) Law norm formulation in article 3 number 11 of government regulation number 53 year 2010 about coming work obligation and obey to the work hour and its description are a vague law norm formulation,  not clear,  not complete and hard to apply and give more dispensation to the high rank official to do more interpretations in the execution. (2) The membership structure of personnel Board (Bapek) based on the government regulation number 53 year 2010 contains of minister and high rank official who has a lot of work to do,  and need much cares,  energies,  times are potential to hinder the Bapek meetings and legality of Bapek decree. (3) Law norm formulation in the head regulation of personnel state board number 21 year 2010 on enclosure of character E about discipline law conveyance number 7 is a vague law norm formulation and not clear.Keywords: Civil Servant Discipline,  Personnel law.